A A Rare Case of Vaginal Leiomyoma on Posterior Vaginal Wall without Uterine Myoma in Chronic Pelvic Pain Patient: A case of vaginal leiomyoma without uterine myoma - Ji, Yong il; Lee, Eun hyun (International Journal of Innovative Research in Medical Science, 2018)
Vaginal leiomyomas (fibromyomas and rhabdomyomas) are rarely reported in literature. They usually present as a vaginal palpable wall mass, or dysparenuria, or pressure symptoms of urinary tract and pelvic organs presentations as pelvic pain. We report one vaginal leiomyoma case found during hysterectomy for relief of chronic pelvic pain. Vaginal leiomyoma is difficult to make accurate diagnosis because of its unusual presentation. Careful examinations and imaging study may need to make differential diagnosis with malignancy.